2013
DOI: 10.1175/bams-d-12-00089.1
|View full text |Cite
|
Sign up to set email alerts
|

NOAA'S Hurricane Intensity Forecasting Experiment: A Progress Report

Abstract: An update of the progress achieved as part of the NOAA Intensity Forecasting Experiment (IFEX) is provided. Included is a brief summary of the noteworthy aircraft missions flown in the years since 2005, the first year IFEX flights occurred, as well as a description of the research and development activities that directly address the three primary IFEX goals: 1) collect observations that span the tropical cyclone (TC) life cycle in a variety of environments for model initialization and evaluation; 2) develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 97 publications
2
66
0
Order By: Relevance
“…Understanding of the HBL structure becomes increasingly important as efforts have been made toward developing high-resolution numerical models in order to improve the hurricaneintensity forecast (e.g., Gopalakrishnan et al 2013;Rogers et al 2013). However, the HBL has been the least observed part of a storm until now, especially its turbulence structure (Black et al 2007;Zhang et al 2008;Zhang 2010).…”
Section: Scientific Highlightsmentioning
confidence: 99%
“…Understanding of the HBL structure becomes increasingly important as efforts have been made toward developing high-resolution numerical models in order to improve the hurricaneintensity forecast (e.g., Gopalakrishnan et al 2013;Rogers et al 2013). However, the HBL has been the least observed part of a storm until now, especially its turbulence structure (Black et al 2007;Zhang et al 2008;Zhang 2010).…”
Section: Scientific Highlightsmentioning
confidence: 99%
“…The nominal grid resolution that is currently used in most models, including some global models, would be sufficient to resolve V 0 1 V 1 for most TCs, because the minimum resolution required for representing this component would be equal to RMW. Observation-based studies have shown that RMW is larger than 20 km for a large majority of the observed TCs (Uhlhorn et al 2013;Rogers et al 2013a). Having the sufficient nominal resolution does not imply that discretization in the model is necessarily adequate for resolving the processes that govern the evolution of the low-wavenumber intensity.…”
Section: Multiscale Intensity Metricmentioning
confidence: 99%
“…Observation-based values of the low-wavenumber intensity could be obtained from SFMR measurements (Uhlhorn et al 2007) as reported by operational and research aircraft reconnaissance in the Atlantic basin during the hurricane season (Aberson 2010;Rogers et al 2013b). Although aircraft reconnaissance data are available for only about 30% of the Atlantic basin TCs (Rappaport et al 2009), the retrospective SFMR data since 1998 include a significant number of diverse TC cases (Table 1).…”
Section: Multiscale Intensity Metricmentioning
confidence: 99%
“…This information is critical for determining the hurricane wavenumber or scale category, from the most devastating Category 5 to the weakest Category 1. The intensity values, in evaluating the destructive effect of hurricane event, are represented in 5-knot (kt) increments at landfall based on Dvorak enhanced infrared (EIR) hurricane techniques and hurricane intensity estimation (HIE) algorithm (Dvorak, 1984;Goodman et al, 2012), and SaffirSimpson Hurricane Wind Scale (Rogers et al, 2013). The unit 'knot' is used to avoid the ambiguity if strength of hurricanes is estimated in mph and km/h, since both metrics have been utilized to define the category or intensity of hurricanes in historical records and may be used for future hurricanes.…”
Section: Introductionmentioning
confidence: 99%